The Semelai Sura and oral history: myth and ideology in an Orang Asli worldview. - Hood Muhamad Salleh (Universiti Kebangsaan Malaysia, 1975)
The principal aim of this paper is to show the continuities existing between an Orang Asli group and social and cultural systems with which this group has been in contact with through time. The main threads of the discussion are brought together through an examination of certain myths and ideological values of the group towards the outside world which reflect the extent of their involvement with it. The purpose of the exercise is to orientate this ethnographical information in the direction of communication with the wider social order (especially Malay society) in order to discard the view that the Orang Asli have been not cognitively and socially aware of social and cultural values of the outside world.